Mapping the role of patient and public involvement during the different stages of healthcare innovation: A scoping review - Victoria Cluley; Alexandra Ziemann; Claire Feeley; Ellinor K. Olander; Shani Shamah; Charitini Stavropoulou (Wiley, 2022)
Abstract Background Patient and public involvement (PPI) has become increasingly important in the development, delivery and improvement of healthcare. PPI is used in healthcare innovation; yet, how it is used has been under‐reported. The aim of this scoping review is to identify and map the current available empirical evidence on the role of PPI during different stages of healthcare innovation. Methods The scoping review was conducted in accordance with PRISMAScR and included any study published in a peer‐reviewed journal between 2004 and 2021 that reported on PPI in healthcare innovation within any healthcare setting or context in any country. The following databases were searched: Medline, EMBASE, CINAHL, PsycInfo, HMIC and Google Scholar. We included any study type, including quantitative, qualitative and mixed‐method studies. We excluded theoretical frameworks, conceptual, scientific or grey literature as well as discussion and opinion papers. Results Of the 87 included studies, 81 (93%) focused on or were conducted by authors in developed countries. A wide range of conditions were considered, with more studies focusing on mental health (n = 18, 21%) and cancer care (n = 8, 9%). The vast majority of the studies focused on process and service innovations (n = 62, 71%). Seven studies focused on technological and clinical innovations (8%), while 12 looked at both technological and service innovations (14%). Only five studies examined systems innovation (5%) and one study looked across all types of innovations (1%). PPI is more common in the earlier stages of innovation, particularly problem identification and invention, in comparison to adoption and diffusion. Conclusion Healthcare innovation tends to be a lengthy process. Yet, our study highlights that PPI is more common across earlier stages of innovation and focuses mostly on service innovation. Stronger PPI in later stages could support the adoption and diffusion of innovation. Patient or Public Contribution One of the coauthors of the paper (S. S.) is a service user with extensive experience in PPI research. S. S. supported the analysis and writing up of the paper.